In vitro fertilization (IVF) and development of mouse embryos - Abdullah, R. B.; Ng, S. Y.; Bakar, F. (Malaysian Journal of Science, 1994)
Fl female mice of 3-4 weeks old derived from the CBA/ca x C57BL/6J strain were superovulated with intraperitoneal injections of 5 1.U. of PMSG and HCG 48 hours apart. At 15 hours after HCG, the oocytes were fertilized with caudal epididymal sperm obtained from males of 10-15 weeks old of CBA/ca x C57BL/6J strain. The insemination concentrations were between 1-2 million sperm cells per mL of medium. At five hours after insemination, the oocytes were washed through a few series of medium changes to remove excess sperm and cumulus cells. The fertilized oocytes were cultured in an incubator in humidified 5% C02 in air at 370C. Embryonic development was recorded until the blastocyst stage. Based on 2-cell stage embryos, fertilization rate of 90.7% was obtained and of the proportion of 2-cell stage embryos, 97.6% developed to the blastocyst stage.